Encontros e desencontros: políticas de memória no município de Toledo - PR (1987-2023) - Trombeta, Rafael Dione (2024)
This work addresses the discourses about the “pioneer” in the municipality of Toledo, located in the western part of Paraná. We analyze the disputes for establishing dates and definitions of what it means to be a “pioneer” of the municipality. In particular, we observe the work of the Willy Barth Historical Museum and the Department of Culture in the formation and maintenance of this identity. For this, we use as a starting point the Pioneer’s Meeting, held since 1987, the guests of this event are identified from registration forms carried out by the aforementioned museum. We will analyze the organization, criteria, and dynamics of the meeting. Finally, we analyze the discourses that construct narratives about the past and the identity of the population of Toledo, published in some local newspapers on the occasion of the Pioneer’s Meetings.